Interspecific differences in toxicological response and subcellular partitioning of cadmium and lead in three earthworm species. (January 2020) - Sinkakarimi, Mohammad Hosein; Solgi, Eisa; Hosseinzadeh Colagar, Abasalt
Abstract: Earthworms are often used as test subjects in toxicological studies, due to their ubiquitousness and sensitivity to contaminant exposure. Such testing is typically conducted using Eisenia fetida as the test subject, but continued use of E. fetida (eco) toxicology is questionable. Therefore, in this study three earthworm species, Aporrectodea rosea, Aporrectodea trapezoides and E. fetida, were exposed to lethal and sublethal concentrations of cadmium (Cd) and lead (Pb) nitrate in artificial soil for 7, 14 and 28 days. A biomarker of genotoxicity (TUNEL assay), biochemical markers [malondialdehyde (MDA) and total antioxidant capacity (TAC)], weight loss, lethal toxicity (LC50 ) and subcellular partitioning were assessed. Cadmium and Pb caused significant inhibition in TAC and growth and significant increases in DNA damage and lipid peroxidation in the earthworms. Acute toxicity rank (14 days) for both Cd and Pb were E. fetida > A. trapezoides > A. rosea . Subcellular partitioning of Cd and Pb in the earthworms were cytosol > debris > granules and debris > granules > cytosol, respectively. Comparison of biomarker responses between study species showed that E. fetida proved to be less susceptible to Cd and Pb exposure than A. rosea and A. trapezoides . Therefore, this study confirms that A. rosea and A. trapezoides are more suitable as subjects than E. fetida for the soil toxicity tests, because of both their greater susceptibility to toxicants and in their abundance in the field. Graphical abstract: Image 1 Highlights: Survival, growth, DNA, MDA and TAC of earthworms were affected during exposure period. A. rosea and A. trapezoides as predominant species showed higher sensitivity than E. fetida. In relatively high concentrations, Cd and Pb showed inhibitory effects on the TAC of earthworms. Main Cd and Pb respectively retrieved from cytosol and debris.